Exploring problem use, discrimination, ethnic identity and social networks. Issue 4 (4th December 2017) - De Kock, Charlotte; Decorte, Tom
Abstract : Purpose: Possessing a strong ethnic identity and ethnic network are described in some epidemiological literature as moderating factors in the relation between perceived discrimination and varying types of substance use in people with a migration background (PMB). The purpose of this paper is to qualitatively explore problem use, discrimination, ethnic identity and social networks in a small purposive sample of users with a Turkish and Eastern European migration background in Ghent, Belgium. Design/methodology/approach: The authors present data retrieved within the framework of a qualitative community-based participatory research study that primarily aims to understand the nature of substance use in PMB. In the secondary analysis, the authors focus on a sub-study examining substance use by people with a Turkish ( n =55) and Eastern European ( n =62) migration background and explore how individuals perceive discrimination, ethnic identity and (ethnic) social networks in 117 qualitative interviews. Findings: Almost all the respondents in this study reported perceived (inter-)ethnic discrimination. The authors establish that problem users in this study have a complex but albeit weak sense of ethnic identity nor do they have a strong ethnic network. This, in combination with perceived discrimination, is a risk factor for continued problem substance use and may hamper recovery related to problem use. Originality/value: This article intends to lay the groundwork for future research that should focus more on longitudinally studying the intertwined relation between problem use, discrimination, ethnic identity and especially social instead of solely ethnic networks, their complex nature as well as their relation to recovery processes among persons with a migration background.